A Study on the Theory of Graphs and Their Applications: Exploring the Relevance and Applications of Graph Theory in Various Fields (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As the theory of Graph becomes increasingly relevant in many fields of mathematics, including science and technology. This applies widely in a number of areas, including biochemical engineering, electrical engineering, IT and operational work. Pure basic findings have been often demonstrated by strong combination methods used in graph theory throughout other fields of mathematics.